2014
DOI: 10.1038/tpj.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

Association of the PDE3A-SLCO1C1 locus with the response to anti-TNF agents in psoriasis

Abstract: Psoriasis is a prevalent autoimmune disease of the skin that causes significant psychological and physical disability. Tumor necrosis factor (TNF)-blocking agents have proven to be highly efficacious in the management of moderate-to-severe psoriasis. However, a significant percentage of patients do not respond to this treatment. Recently, variation at the PDE3A-SLCO1C1 (phosphodiesterase 3A-SoLute Carrier Organic anion transporter family member 1C1) locus has been robustly associated with anti-TNF response in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41][42][43] For all significant associations, except TLR9 (rs352139) and LY96 (rs11465996), similar tendencies were observed for ORs for each of the anti-TNF agents (data available on request). To our knowledge, this is one of the largest cohorts for evaluation of response in patients treated with ustekinumab 44,45 and the second largest for evaluation of anti-TNF; only a Canadian study (also involving treatment primarily for psoriatic arthritis) had more patients.…”
Section: Study Populationmentioning
confidence: 68%
“…[33][34][35][36][37][38][39][40][41][42][43] For all significant associations, except TLR9 (rs352139) and LY96 (rs11465996), similar tendencies were observed for ORs for each of the anti-TNF agents (data available on request). To our knowledge, this is one of the largest cohorts for evaluation of response in patients treated with ustekinumab 44,45 and the second largest for evaluation of anti-TNF; only a Canadian study (also involving treatment primarily for psoriatic arthritis) had more patients.…”
Section: Study Populationmentioning
confidence: 68%
“…Patients who were homozygous for the LCE3B/3C deletion, another known risk variant for psoriasis, had a less favourable response to anti‐TNF agents . Pharmacogenetic associations were also reported for genetic variants in the following susceptibility genes: CARD14 , CDKAL1 , FCGR3A and PDE3A‐SLCO1C1 (File S6; see Supporting Infromation) …”
Section: Resultsmentioning
confidence: 92%
“…Five studies investigated pharmacogenetics for adalimumab . Contrary to TNF inhibitors as a group, none of the SNPs in TNF‐α‐related genes were significantly associated with a response to adalimumab individually.…”
Section: Resultsmentioning
confidence: 99%
“…FCGR3A rs396991 was also evaluated by Mendrinou et al who showed that T allele could be a marker of beter response to etanercept [58]. Moreover, a positive association was found between PDE3A-SLCO1C1 rs3794271AA genotype and PASI score in patients treated with etanercept [59]. Association between the CD84 genotypes and response to biologics was also evaluated.…”
Section: Pharmacogenetics Of Anti-tnfα Treatmentmentioning
confidence: 99%